Effect Of Addition Of Butterfly Pea Flower Powder (Clitoria Ternatea Linn) On Total Lactic Acid Bacteria, Lactic Acid and Ph Of Goat Milk Kefir Whey - Ummah, Ajizah Khoirul; Sumarmono, Juni; Hantoro Djoko Rahardjo, Agustinus (Bulletin of Applied Animal Research, 2022)
The purpose of this study was to determine the effect of the addition of butterfly pea flower powder on total lactic acid bacteria (LAB), lactic acid levels and pH whey kefir goat milk. The research materials used included 12000 g of goat milk, 240 g of kefir grains and 150 g of butterfly pea flower powder. The experiment was performed using a Complete Randomized Design (CRD) with 6 treatments and 4 replicates. Treatments applied include the addition of butterfly pea flower powder 0%, 0.5%, 1%, 1.5%, 2% and 2.5% (w/w) milk. The variables measured were total LAB (CFU/ml), lactic acid levels (%) and pH of whey kefir. Data were analyzed for variance and further tested using polynomial orthogonal. The results showed that the addition of butterfly pea flower powder did not affect the BAL population, had a significant effect on lactic acid levels and had a very noticeable effect on the pH of goat milk whey kefir. The population of LAB ranged from 9.23±0.09 log CFU/ml to 10.23±1.14 log CFU/ml, lactic acid levels of 1.29±0.36% to 2.19±0.66% and pH ranged from 3.50±0.36 to 3.68±0.37. In conclusion, the addition of butterfly pea flower powder on goat milk whey kefir increases lactic acid content and lower the pH value of goat milk whey kefir, without inhibiting LAB growth. The addition of butterfly flower powder is recommended as much as 0.5% (w/w) of the total goat milk used to make kefir.